ORGANIZATIONAL EFFECTIVENESS OF THE PROCUREMENT SERVICE SECTION OF SOUTH OF TANGERANG CITY - Arie Kurniawan; Retnowati Tuti; Ma’mun Murod; Evi Satispi; Djoni Gunanto (Universitas Muhammadiyah Jember, 2021)
Procurement of goods and services that are in government with limited resources and regulations that change according to the times of course these change will affect organizational effectiveness. In such an environment the procurement of goods and services must be responsive and clever in anticipating to maintain their existence and function. For an organization to maintain its existence and function, it must be effective to support this the South Tangerang City Procurement Service Section has an important contribution in the implementation of the goods or services procurement process. Based on these conditions a research was conducted with the title: